Geographic Disparities in Patient Travel for Dialysis in the United States. Issue 4 (11th April 2013) - Stephens, J. Mark; Brotherton, Samuel; Dunning, Stephan C.; Emerson, Larry C.; Gilbertson, David T.; Harrison, David J.; Kochevar, John J.; McClellan, Ann C.; McClellan, William M.; Wan, Shaowei; Gitlin, Matthew
Abstract Purpose To estimate travel distance and time for US hemodialysis patients and to compare travel of rural versus urban patients. Methods Dialysis patient residences were estimated from ZIP code‐level patient counts as of February 2011 allocated within the ZIP code proportional to census tract‐level population, obtained from the 2010 US Census. Dialysis facility addresses were obtained from Medicare public‐use files. Patients were assigned to an "original" and "replacement" facility, assuming patients used the facility closest to home and would select the next closest facility as a replacement, if a replacement facility was required. Driving distances and times were calculated between patient residences and facility locations using GIS software. Findings The mean one‐way driving distance to the original facility was 7.9 miles; for rural patients average distances were 2.5 times farther than for urban patients (15.9 vs 6.2 miles). Mean driving distance to a replacement facility was 10.6 miles, with rural patients traveling on average 4 times farther than urban patients to a replacement facility (28.8 vs 6.8 miles). Conclusion Rural patients travel much longer distances for dialysis than urban patients. Accessing alternative facilities, if required, would greatly increase rural patient travel, while having little impact on urban patients. Increased travel could have clinical implications as longer travel is associated with increased mortality and decreased quality of life.